Optimization and Thermodynamic Analysis of CO2 Refrigeration Cycle for Energy Efficiency and Environmental Control - Manish Hassani and Kamlesh Purohit (Nature Environment and Pollution Technology)
Supermarket applications are significant contributors to greenhouse gas emissions, necessitating efforts to reduce carbon footprints in the food retail sector. Carbon dioxide (R744) is recognized as a viable long-term refrigerant choice due to its favorable properties, including low Global Warming Potential, non-toxicity, non-flammability, affordability, and widespread availability. However, enhancing the energy efficiency of pure CO2 systems in basic architecture units, particularly in warm regions like India, remains a challenge. To address this, modern refrigeration systems must prioritize low energy consumption and high coefficient of performance (COP) while meeting environmental standards. This study investigates different operating conditions to determine the optimal parameter range for maximizing COP and improving the efficiency of conventional CO2 refrigeration configurations. It examines both subcritical and transcritical refrigeration cycles under varying parameters, emphasizing the importance of understanding COP’s relationship with factors such as subcooling, superheating, ambient temperature, and evaporator temperature. The study advises against superheating in CO2 systems but highlights the substantial COP increase with higher degrees of subcooling, leading to enhanced system performance. Additionally, it provides a comprehensive theoretical comparison between advanced pure CO2 supermarket applications and commonly used hydrofluorocarbons-based systems, offering insights into energy efficiency and environmental impacts for informed decision-making in the industry.